High-Throughput Mechanobiology Screening Platform Using Micro- and Nanotopography - Hu, J; Gondarenko, A; Dang, A; Bashour, K; O'Connor, R; Lee, S; Liapis, A; Ghassemi, S; Milone, M; Sheetz, M; Dustin, M; Kam, L; et al. (American Chemical Society, 2016)
We herein demonstrate the first 96-well plate platform to screen effects of micro- and nanotopographies on cell growth and proliferation. Existing high-throughput platforms test a limited number of factors and are not fully compatible with multiple types of testing and assays. This platform is compatible with high-throughput liquid handling, high-resolution imaging, and all multiwell plate-based instrumentation. We use the platform to screen for topographies and drug-topography combinations that have short- and long-term effects on T cell activation and proliferation. We coated nanofabricated "trench-grid" surfaces with anti-CD3 and anti-CD28 antibodies to activate T cells and assayed for interleukin 2 (IL-2) cytokine production. IL-2 secretion was enhanced at 200 nm trench width and >2.3 μm grating pitch; however, the secretion was suppressed at 100 nm width and <0.5 μm pitch. The enhancement on 200 nm grid trench was further amplified with the addition of blebbistatin to reduce contractility. The 200 nm grid pattern was found to triple the number of T cells in long-term expansion, a result with direct clinical applicability in adoptive immunotherapy.